2020
DOI: 10.1039/c9ta10543c
|View full text |Cite
|
Sign up to set email alerts
|

Approaching the Shockley–Queisser limit for fill factors in lead–tin mixed perovskite photovoltaics

Abstract: A new post-treatment method for lead–tin mixed perovskites enabling device fill factors approaching 83%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…Also, a post-treatment on perovskite films by toluene rinsing has been reported to further remove Sn(IV). [17] To uncover the toluene rinsing effect on solar cell performance and differentiate it from the EDA coating effect, we analyzed the PCE of devices without EDA coverage. Little improvement in PCE was noticed which can be ascribed to better FF, however, no change in V oc was noticed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a post-treatment on perovskite films by toluene rinsing has been reported to further remove Sn(IV). [17] To uncover the toluene rinsing effect on solar cell performance and differentiate it from the EDA coating effect, we analyzed the PCE of devices without EDA coverage. Little improvement in PCE was noticed which can be ascribed to better FF, however, no change in V oc was noticed.…”
Section: Resultsmentioning
confidence: 99%
“…[13] In another work, the surface passivation of Sn-Pb perovskite films by phenethylammonium (PEA) cation has been described that led to the formation of a 2D capping layer resulting in the stability of the films against oxidation. [14] Jayawardena et al, [17] also revealed the passivation effect of guanidinium bromide (GuaBr) leading to the better energy alignment between the perovskite and electron transport layer which enhances the fill factor drastically near to the SQ limit. It is well known that the better energy alignment between perovskite and charge transport layers is key in improving the PSC performance due to the reduction in carrier recombination and the better charge transfer at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…In most other reports, PbSn perovskites with similar bandgaps delivered even lower short‐circuit current (<30 mA cm –2 ). [ 17–19 ] This discrepancy between two apparently similar technologies is not often discussed and it is currently not clear why Sn(II) containing perovskites cannot achieve as high currents as their lead counterparts relative to their SQ limits.…”
Section: Introductionmentioning
confidence: 99%
“…introduced GABr as an additive into Cs 0.05 FA 0.79 MA 0.16 Pb 0.5 Sn 0.5 I 3 perovskites. [ 112 ] The post‐treatment with GABr modified the band alignment and contact of the perovskite/HTL and perovskite/ETL interfaces, enabling better bipolar extraction. The resulting shifts in the conduction band, valence band and Fermi level energies reduce the barrier for both hole and electron transfer from the LTM perovskite absorber to the anode and cathode contacts.…”
Section: Sn‐based Perovskite Solar Cellsmentioning
confidence: 99%
“…The atomic percentage of Sn 4+ decreases in the order of anisole > CB> toluene, and the device performance increases in the order of anisole < CB < toluene, which is further substantiated by the lower impact of parasitic charges for lead‐tin mixed (LTM) PSCs under toluene treatment. [ 112 ] As a result, the champion efficiency they achieved is 11.6%, and the short circuit current density is ∼28 mAcm −2 .…”
Section: Sn‐based Perovskite Solar Cellsmentioning
confidence: 99%